Hubungan Ekspresi Ki-67 dan E-Cadherin dengan Kedalaman Invasi Melanoma Malignum Berdasarkan Clark Level - Santy Saberko; Salmiah Agus; Satya Wydya Yenny (Majalah Patologi Indonesia, 2019)
BackgroundMalignant melanoma (MM) is a neoplasia derived from melanocytes. This is the most aggressive cancer ofskin. Even small tumors may have a tendency to metastasize and thus lead to a relatively unfavorableprognosis. Malignant melanoma depth of invasion based on Clark level is one of the important prognosticfactors to determine survival rate of MM patient. Determination of invasion based on this Clark level issubjective, more objective checks such as Ki-67 and E-Cadherin are required. This examination isexpected to see the risk of metastasis in MM. Cell proliferation is the main key for tumor progression and itcan be measured with Ki-67 expression. E-cadherin is one of transmembrane protein that plays importantrole in metastasis. The purpose of this study is to determine correlation between Ki-67 and E-Cadherinexpression with depth of invasion of malignant melanoma based on Clark level.MethodsThis is cross sectional study in Padang and Jakarta, with 42 cases of malignant melanoma which havebeen diagnosed in Pathology Anatomic Laboratory in West Sumatera. Samples were obtained fromparaffin block of or tissue from surgery and have been reviewed depth of invasion based on the Clark level.These samples were divided into I-V Clark level group. Ki-67 expression of cells nuclei and expression ofE-Cadherin of cells membrane were analyzed using immunohistochemistry assay. One Way Annovabivariate statistical analysis were used and value p<0.05 were considered significant.ResultsPositive Ki-67 expression were found in 42 cases, 6 samples with II Clark level, 8 samples with III Clarklevel, 19 samples with IV Clark level, 9 samples with V Clark level. Malignant melanomas were mostlyfound in male 60-79 age group and depth of invasion in IV Clark level. Positive E-Cadherin expression in IIClark level. There was significant correlation between Ki-67 and E-Cadherin